Site-directed mutagenesis of the simian virus 40 large T-antigen gene: replication-defective amino acid substitution mutants that retain the ability to induce morphological transformation. - Peden, K W (1985)
We used a heteroduplex deletion loop mutagenesis procedure for directing sodium bisulfite-induced mutations to specific sites on viral or plasmid DNA to generate a series of SV40 large T-antigen point mutants. The mutations were directed to a region of the T-antigen gene, 0.5 map units, that is thought to be important for interaction of the protein with the viral origin of DNA replication. Of the 16 mutants reported here, 10 had lost the ability to replicate their DNA, and 3 others showed a reduced level of replication compared to wild type. All of the mutants tested were capable of transforming rat cells in culture by the dense focus assay. We conclude that the sequences of the early region around 0.5 map units are critical for the replication of viral DNA but not for the transformation function of T antigen.